STRENGTHENING LOCAL FOOD SECURITY THROUGH COMMUNITY EMPOWERMENT IN THE PRODUCTION OF MALIKA BLACK SOYBEANS IN TULANG BAWANG REGENCY - Ahmad Ratib Asraf Triputra; Goestyari Kurnia Amantha; Ulfa Umayasari (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Food security does not only on the government's role in its management. Collaboration among the government, private sector, and society is also essential in achieving food self-sufficiency. Food security is not merely about national-scale food production, but also about regional initiatives capable of developing local potential independently and consistently. This study examines efforts to strengthen local food security through community empowerment in the production of Malika black soybeans in Tulang Bawang Regency. As an alternative and relatively new food commodity with high nutritional value and significant economic potential, Malika black soybeans offer opportunities for sustainable agriculture and increased farmer income. Using a descriptive qualitative approach and a case study method, this research analyzes the partnership model between the Tulang Bawang Regency Government and PT Horti Yasmin Jaya in the production of Malika black soybeans. Preliminary results show that the first harvest was successfully carried out despite challenges such as land suitability and planting distance. This collaboration serves as a concrete example of an inclusive food governance strategy, promoting farmer independence and increasing the added value of local commodities as part of regional food security.